Destabilizing the AXH Tetramer by Mutations: Mechanisms and Potential Antiaggregation Strategies - Grasso, Gianvito (Biophys J, 2018)
The AXH domain of protein Ataxin 1 is thought to play a key role in the misfolding and aggregation pathway responsible for Spinocerebellar ataxia 1. For this reason, a molecular level understanding of AXH oligomerization pathway is crucial to elucidate the aggregation mechanism, which is thought to trigger the disease. This study employs classical and enhanced molecular dynamics to identify the structural and energetic basis of AXH tetramer stability. Results of this work elucidate molecular mechanisms behind the destabilizing effect of protein mutations, which consequently affect the AXH tetramer assembly. Moreover, results of the study draw attention for the first time, to our knowledge, to the R638 protein residue, which is shown to play a key role in AXH tetramer stability. Therefore, R638 might be also implicated in the AXH oligomerization pathway and stands out as a target for future experimental studies focused on self-association mechanisms and fibril formation of full-length ATX1.